Pilot examination of stress, heart rate variability, and alcohol craving and use among female veterans - Holzhauer, Cathryn Glanton; Epstein, Elizabeth E.; Bickar, Laurel; Ellis, Robyn A.; Pole, Nnamdi; Sofuoglu, Mehmet; Smelson, David A.; Mattocks, Kristin (Frontiers in Psychiatry, 2022)
Rates of alcohol use disorder (AUD) are increasing among civilian and veteran populations of women in the United States, and stress pathophysiology (i.e., abnormal acute and long-term change in physiological responses to stress) is central to the maintenance of alcohol misuse within this population. Heart rate variability (HRV) is one measure of stress regulation that may help to explain the association of stress with alcohol misuse among women. In the current analysis of pilot data, 20 women veterans attended an in-person laboratory session and completed 35 daily assessments of their alcohol use and craving. During the lab session, the effects of a stress induction procedure on self-reported alcohol craving and HRV were assessed. HRV was continuously measured and indexed in the time domain, using the root mean square of successive differences between normal heartbeats (RMSSD). Alcohol craving and use during the longitudinal 35-day study period were measured via self-report questionnaires sent to participants’ phones. Results indicated that resting HRV in the lab was positively associated with odds of daily craving. Moreover, HRV during the stressor, as measured in lab, was positively associated with (1) overall alcohol craving in the lab (i.e., with resting and post-stress craving), and (2) number of daily drinks during the 35-day study period. This pilot study suggests the potential role of HRV in response to stressors in predicting alcohol craving and use among female veterans. It provides pilot data for research on stress-reactive HRV as a biomarker for alcohol misuse among women, and discusses directions for future research.